(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Herbal formulations play an important role in medicines; however, their suboptimal standardization, in terms of identity, purity, quality, efficacy and safety, has questioned their efficiency in treating various disorders. The present study was conducted to perform a quality audit of two herbal formulations, i.e., ashokarishta syrup and chandraprabha vati, of three different marketed brands. The quality auditing procedures included analysis of moisture content, ash value, pH, presence of heavy metals, pesticide residue, radioactive substances and microbial contamination. The formulations were pharmacologically evaluated for anti-inflammatory activity using the rat paw edema model. All the formulations passed the microbial contamination test. None of the heavy metals was detected with higher than permissible limits in any formulations. Moreover, all the formulations were found free from pesticides and radioactive substances. In addition, the formulations also possessed anti-inflammatory activity; however, their activity varied among brands. The present study concluded that all the formulations tested were successfully quality audited. This study can be used as a standardizing tool for the future perspective.